Framework for Enhancing the Performance of Unit Testing in Java Based Projects - Sharma, Amit (My University, 2015)
This age is information technology age. We are living in a world where everything is handled by computers, smartphones and other software based systems. The dependency on software systems has increased to a great extent. The complexity of softwares has become very high these days since the software is supposed to serve for multiple functionalities. Earlier the softwares were not that complex and it was easy to develop the software so the software developers did not have much overhead regarding the product to be developed. As the complexity of the softwares increases the logic which is required to develop the software also becomes more complicated which ultimately results in a very complex code required for the software. The motive of this introduction is to explain that the coding part of the softwares has become very complex now. Developing and maintaining such complex code is not an easy task. In order to make sure the written code is working correctly and to make it reliable and sustainable, one of the software testing technique which is called as unit testing is used. As the complexity of the code has grown quite high, resulting in a very large code base, so the number of unit test cases which are needed to be implemented has become very high. In order to make sure whole code is working fine, all the unit test cases should be executed successfully before moving the code to the next phase of development cycle. Now the main overhead in this case is executing all the unit test cases one by one manually. Since there is a very high number of test cases, so if all the test cases are executed one by one manually then it will not only require lots of human effort but also it needs very high amount of time, which is not feasible. This thesis presents a framework to make this process automated for java based projects. Using the suggested algorithm all the execution process of unit test cases become automated. After implementing the framework, the developer only needs to write code and the required unit test cases but there is no need to execute all the test cases manually. The complete execution process is taken care by the framework. This will not only save human effort but also reduces the execution time of the unit test cases which enhances the performance of development process.
M.E. (CSED)
Keywords: Unit Testing; Java; ANT script